Development of a novel nanoparticulate carrier system for enhancement of bioactive molecule delivery into the brain - Huda, Naz Hasan (Curtin University, 2017)
The development of a biocompatible dual ligand PEGylated poly(D,L-lactide-co-glycolide) nanoparticulate drug delivery system to enhance delivery into the brain. Nanoparticulate formulations containing the drug rivastigmine had physicochemical characteristics ideal for targeting the brain and negligible cytotoxicity. Cell uptake and transport were superior to the drug solution or nanoparticles without the ligand targeting technology. This dual ligand NP drug delivery system is a potential platform technology for brain delivery for a range of therapeutic outcomes.